The enrich marital satisfaction scale: adaptation and psychometric properties among at-risk and community Portuguese parents - Nunes, Cristina (2022)
Marital satisfaction is a multidimensional construct that encompasses the satisfaction with marital interactions and with the emotional and the practical aspects of marriage. Marital satisfaction has a great impact on personal well-being and affects the family as a whole; low marital satisfaction has been associated with unhappiness and with higher divorce rates. Furthermore, marital satisfaction is related with family functioning and is an indicator of the quality of the parenting relationship. The Enrich Marital Satisfaction (EMS) scale is a two-factor and 15-items self-report measure that assesses satisfaction with the marital relationship. This study analysed the psychometric properties of the EMS among two samples: at-risk (N = 273, M = 37.05 years, 82.05% women) and community (N = 205, M = 38.38 years, 52.2% women) Portuguese parents. Participants completed the EMS and measures of parenting sense of competence, parenting stress, and parenting alliance. Confirmatory factor analyses showed that the revised two-factor model obtained the best fit, after removing a few items. Measurement invariance across the two samples was demonstrated. The EMS showed good psychometric properties, namely internal consistency, convergent and discriminant validity. The EMS is a time-efficient tool for both researchers and practitioners who need to assess marital satisfaction, a relevant dimension for family functioning and parenting.